Pengembangan E-LKPD Berintegrasi Microscale Lab menggunakan Budaya Mamaq pada Materi Asam Basa Kelas XI - Mahendra, Riza; Junaidi, Eka; Arian Sani Anwar, Yunita (Chemistry Education Practice, 2025)
This research aims to develop chemistry learning media by integrating a small-scale laboratory (microscale lab) using the mamaq culture approach to improve students' conceptual understanding of acid-base material. This research is a development research with a 4D model design (Define, Design, Develop, Disseminate). The media developed is a Student Worksheet in electronic form (E-LKPD) which is uploaded to the website, making it easy to access and allowing the addition of images and learning videos related to acid-base material by associating it with mamaq culture. In addition, this E-LKPD also contains quizzes, sample questions, and evaluations to measure students' understanding of the material studied. This LKPD was developed using an experimental approach, integrated with a small-scale laboratory that allows practicum outside the lab with smaller tools and materials without reducing the essence of the practicum. This medium has been validated by two validators using a validation questionnaire, and the data was analyzed with an average formula, resulting in a score of 3.32 in the very valid category. Furthermore, a trial was carried out to assess the practicality of this media, by collecting responses from teachers and students. The results of the practical test showed a score of 91% from teachers and 85% from students, both in the very valid category.